Metodología para la aplicación de una audioría de getión en las empresas administradoras de fondos y fideicomisos caso: Fideval S.A. Administradora de Fondos y Fideicomisos, año 2014 - Naranjo Solis, Jefferson Fernando (2015)
The development of this work is meant to be a methodological guide for assessing corporate governance and trust fund managers in order to provide basic tools that allow those in charge of internal control of the same or others interested to evaluate, analyze and improve processes such organizations. The work was done by understanding and evaluation of the institution through audit procedures and tools. The following are the chapters to be treated described. Chapter 1, deals with the analysis of the audit starting from a general knowledge to a more particular theoretical, conceptual and practical framework that is applied to conduct the study in the institution is analyzed. Chapter 2 focuses on the knowledge of the company Fideval S.A., fund manager and trusts, while situational described through analysis of its objectives, internal policies, controls, regulations, manuals, instructional, organizational structure, SWOT matrix and other regulatory mechanisms that may explain to the business. Chapter 3, describes a practical methodology to conduct audits in these businesses, in order to propose a set of techniques and methods to help make a critical, systematic review, and impartial in the management of an entity and thus to determine their efficiency and effectiveness in managing their resources in order to provide findings and recommendations suggest that optimize power management Fideval SA..